Are inner disc misalignments common? ALMA reveals an isotropic outer disc inclination distribution for young dipper stars. Issue 1 (2nd December 2019) - Ansdell, M; Gaidos, E; Hedges, C; Tazzari, M; Kraus, A L; Wyatt, M C; Kennedy, G M; Williams, J P; Mann, A W; Angelo, I; Dûchene, G; Mamajek, E E; et al.
ABSTRACT: Dippers are a common class of young variable star exhibiting day-long dimmings with depths of up to several tens of per cent. A standard explanation is that dippers host nearly edge-on ( i d ≈ 70°) protoplanetary discs that allow close-in (<1 au) dust lifted slightly out of the mid-plane to partially occult the star. The identification of a face-on dipper disc and growing evidence of inner disc misalignments brings this scenario into question. Thus, we uniformly (re)derive the inclinations of 24 dipper discs resolved with (sub-)mm interferometry from ALMA. We find that dipper disc inclinations are consistent with an isotropic distribution over i d ≈ 0−75°, above which the occurrence rate declines (likely an observational selection effect due to optically thick disc mid-planes blocking their host stars). These findings indicate that the dipper phenomenon is unrelated to the outer (>10 au) disc resolved by ALMA and that inner disc misalignments may be common during the protoplanetary phase. More than one mechanism may contribute to the dipper phenomenon, including accretion-driven warps and 'broken' discs caused by inclined (sub-)stellar or planetary companions.